Dynamic obstacle detection and avoidance for mobile robots - Radhika Ramachandran (2014)
Obstacle avoidance is one of the key issues in robot motion planning. It is one of the critical issues especially because of the extensive use of unmanned vehicles in urban areas and for military purposes. During the course of its motion, a robot will have to deal with both static and dynamic obstacles. Some examples of static obstacles are buildings, trees, furniture etc. People, vehicles, other robots etc are the dynamic obstacles that the robot may encounter. For safe and unobstructed motion of the robots, timely detection and avoidance of these obstacles is extremely important. This thesis addresses this issue of obstacle avoidance for a mobile robot equipped with a laser range finder.